PENGGUNAAN LARUTAN DAUN SIRIH (Piper betle L) DENGAN DOSIS YANG BERBEDA UNTUK MENCEGAH PERTUMBUHAN JAMUR (Saprolegnia sp) PADA TELUR IKAN TAWES (Puntius javanicus) - Syarifah Zuraidah; Silkhairi Silkhairi (JURNAL PERIKANAN TROPIS, 2016)
The research about of solution betel leaf (Piper betle L) With Different Doses To prevent the growth of fungi (Saprolegnia sp) on fish eggs Tawes (Puntius javanicus) are funded on June 18 to 21 Mai 2015 Meunasah Krueng Village housed in Beutong Subdistrict Nagan Raya District, aims to find out the dose of solution effective betel leaves to prevent fungal attack on fish eggs tawes so it can increase the power of fish eggs tetas tawes (Punius javanicus). The method used is an experimental method that is giving preferential treatment to solution the betel leaf with different doses against fish eggs tawes. Research results percentage of hatching eggs in each treatment varies. The highest hatching there is treatment 1 (10 ml) with the average results achieved (93,33%), followed by treatment 2 (20 ml) of (83,33%), treatment 3 (30 ml) of (66,6%) and the lowest percentage of hatching there is at treatment 0 (0 ml) or control (50%). And on testing statistics retrieved that F count (65,33) > F table of 0.01 (7.59), meaning a very real effect. Test BNT (Least Significant Difference) showed that the use of betel leaf solution with a dose of 10 ml (treatment 1) gave the best results and treatment 0 (control) the lowest hatching percentage